Análise das auditorias de tecnologia da informação realizadas pelos tribunais de contas dos estados e Distrito Federal - Souza, Ramon Jorge de (2018)
In a scenario in which IT consumes a large part of the budget and therefore must be well managed in order to avoid unnecessary waste and expense, always focusing on efficiency, effectiveness and cost-effectiveness. In this way, IT needs to be subject to control actions, in order to ensure that the information criteria are met, contributing to the improvement of public services and to the prevention of irregularities, deviations and losses of public resources. As auditing is one of the main instruments of audit of the courts of accounts, this work sought, as a general objective, to analyze the audits of Information Technology carried out by the Audit Courts of the States and the Federal District. A qualitative and descriptive survey was carried out based on the IT audit reports of these courts from 2011 to 2016. The results show that the courts have concentrated their activities in the area of procurement and IT contracts and applications, but it doesn’t operate in important areas such as data and communication networks. The main problems identified in the audits were the lack of information security plans, poor planning for IT hiring, problems in the accessibility and usability of government systems and portals, divergent, inconsistent or incomplete information in systems and making undue payments or even over-invoicing in procurement of IT resources. In addition, the courts indicated proposals for a solution to improve public management, mainly requesting the implementation of internal controls by their jurisdictions.